(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article presents and analyzes the results obtained from an experimental study of the content of toxic components in the exhaust gases during the operation of a car engine with gasoline and liquefied petroleum gas (LPG). The study was conducted in laboratory conditions by loading the driving wheels with a roller-type chassis dynamometer, corresponding to the established movement of the car with constant speed on a horizontal road section.